2019
DOI: 10.1210/jc.2018-02346
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical Cord miRNAs in Small-for-Gestational-Age Children and Association With Catch-Up Growth: A Pilot Study

Abstract: Context Catch-up growth in infants who are small for gestational age (SGA) is a risk factor for the development of cardiometabolic diseases in adulthood. The basis and mechanisms underpinning catch-up growth in newborns who are SGA are unknown. Objective To identify umbilical cord miRNAs associated with catch-up growth in infants who are SGA and study their relationship with offspring’s cardiometabolic parameters. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…In addition to such evidence for gestational hyperandrogenism contributing to PCOS etiopathogenesis, gestationally diabetic in utero environments [64][65][66][67], as well as poor intrauterine nutrition and fetal growth restriction [67][68][69], contribute developmental, likely epigenetic [37,70,71], programming to women with PCOS. Human placentae readily convey maternal glucose to the fetus engaging a progressively maturing fetal pancreatic beta cell response, but preventing transfer of maternal insulin [72].…”
Section: The Evidence For Developmental Origins Of Pcos From Clinicalmentioning
confidence: 99%
“…In addition to such evidence for gestational hyperandrogenism contributing to PCOS etiopathogenesis, gestationally diabetic in utero environments [64][65][66][67], as well as poor intrauterine nutrition and fetal growth restriction [67][68][69], contribute developmental, likely epigenetic [37,70,71], programming to women with PCOS. Human placentae readily convey maternal glucose to the fetus engaging a progressively maturing fetal pancreatic beta cell response, but preventing transfer of maternal insulin [72].…”
Section: The Evidence For Developmental Origins Of Pcos From Clinicalmentioning
confidence: 99%
“…This study demonstrated that prepregnancy underweight (at any GWG level) or appropriate pBMI but with inadequate GWG was associated with the ‘no catch‐up growth’ pattern that was consistent with former studies showing that inadequate GWG was associated with a higher incidence of SGA birth (Goldstein et al, 2017 ; Li et al, 2013 ; Siega‐Riz et al, 2009 ). Children whose weights were less than the 10th percentile from birth to 7 years of age were labelled as the children with the ‘no catch‐up growth’ pattern and were at an increased risk for cerebral palsy, cognitive delay and cardiometabolic diseases (Mas‐Parés et al, 2019 ; Takeuchi et al, 2018 ). Findings in this study were also consistent with previous studies reporting that the offspring of the mothers having lower weight gain during pregnancy had lower body weights at adulthood (Goldstein et al, 2017 ; Gurugubelli Krishna & Vishnu Bhat, 2018 ; Radford et al, 2014 ), and inadequate GWG was associated with a higher risk of stunning at 5 years old (Xie et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with data reported by Tang et al (2013) who found a significant positive correlation between mRNA expression of PLAG1 and level of IGF2 in placental tissues of fetal growth retardation compared to controls. Moreover, a downregulation of miR-16 and miR-21 in the placenta was significantly related with lower birth weight (Maccani and Marsit, 2011).…”
Section: Mirnamentioning
confidence: 92%
“…miRNA serum profile in umbilical cord of SGA children with (SGA-CU, n = 18) and without catch-up growth (SGA-nonCU, n = 24) was investigated (Mas-Parés et al, 2018). In particular, 12 miRNA were differentially expressed between SGA-CU and SGA-nonCU (miR-128-3p, miR-222-5p, miR-300, miR-374b-3p, miR-501-3p, miR-548c-5p, miR-628-5p, miR-770-5p, miR-873-5p, miR-876-3p and miR-940).…”
Section: Mirnamentioning
confidence: 99%